Odpowiedzi

Najlepsza Odpowiedź!
2009-10-22T19:19:31+02:00
A)6ax+4ay+15bx+10by=2a(3x+2y)+5b(3x+2y)
b)6ax-3ay-4bx+2by=3a(2x-y)-2b(2x-y)

a)8(3.5-0,5)-3.5(7-b)=24-24.5+3,5b=-0.5+3.5b
b) a-b(a+b)(2a-b)=1.5-0.5×2×2.5=-1
2009-10-22T19:30:58+02:00
A)6ax+4ay+15bx+10by=
=2a(3x+2y)+5b(3x+2y)=
=(3x+2y)(2a+5b)
b)6ax-3ay-4bx+2by=
=3a(2x-y)-2b(2x-y)=
=(2x-y)(3a-2b)
zad.2
oblicz wartośc liczbowej wyrażeń:
a) 8(a-0,5)-a(2a-b) dla a =3,5
8a-4-2a²+ab
8*3,5-4-2(3,5)²+3,5b=
=24-24,5+3,5b=
=-0,5+3,5b
b)a-b(a+b)(2a-b) dla a=1,5 b=0,5
a-b(2a²-ab+2ab-b²)
1,5-0,5(4,5-0,75+1,5-0,25)=
=1,5-0,5(5)=
=1,5-2,5=-1
2009-10-22T19:40:19+02:00
1
a) 2a(3x+2y)+5b(3x+2y)=(3x+2y)(2a+5b)
b) 3a(2x-y)-2b(2x-y)=(2x-y)(3a-2b)